How supermarket retailers value business outcomes of healthy food retail strategies: a discrete choice experiment - Alsubhi, Moosa; Blake, Miranda R.; Livingstone, Ann; Moodie, Marj; Ananthapavan, Jaithri (Frontiers in Public Health, 2024)
BackgroundSupermarkets are businesses, and any voluntary changes to increase the healthiness of their food offerings must align with retailers’ commercial needs. Business outcomes of healthy food retail strategies are important non-health factors that may influence retailers’ decisions to implement these strategies. Although there is growing evidence on the significance of various business outcomes, such as net profit and customer satisfaction, it remains unclear how retailers value and trade-off these outcomes against each other. This study aimed to determine retailer preferences and measure their marginal willingness to pay for key business outcomes.MethodsA Discrete Choice Experiment (DCE) survey recruited current or former owners or managers of supermarkets or grocery stores in Australia. It included 12 choice tasks for two hypothetical scenarios (A or B) that the retailer could implement in their store, along with an option to maintain the current situation (opt-out option). The survey included six attributes (net profit, healthy items sold, customer and retailer satisfaction, ease and costs of implementation) with 3–4 levels each. A multinomial logit model was used to estimate preferences and calculate marginal rates of substitution and marginal willingness to pay.ResultsSixty-one respondents completed the DCE, resulting in a 72% response rate. Retailers identified customer satisfaction as the highest ranked business outcome when deciding to implement healthy food retail strategies. This was followed by the percentage of healthy items sold, supplier satisfaction, net profit, implementation cost, and ease of implementation. The marginal willingness to pay for different attribute levels varied from A650 per year per store for a strategy that increases net profit by 3% to A32,136 for a strategy leading to “very satisfied” levels of customer satisfaction compared to the base level.ConclusionThe results could be used to guide the implementation of healthy food retail strategies that also meet the needs of retailers.